1860-61 N.C. Sess. Laws 219-20 - (:unkn) unknown (My University, 1860)
Priv. Laws, ch. 180, § 1: Granted the town of Wilmington the authority to levy and collect taxes annually on all pistols, dirks, Bowie-knives, or sword-canes if worn about the person at any time during the year, as well as all pistol galleries.
Keywords: SHOOTING RANGES OR GALLERIES; TAX - PROPERTY OR SALES